Parametrização, zoneamento e produção autônoma do espaço urbano - Henrique Gazzola de Lima (2017)
The research discusses some novel possibilities brought by parameterization in the production of urban space. By operating at the level of the structure of a system or process, defining constraints and degrees of freedom through parameters and explicit relations, parameterization can be directed to the creation of supports for decisions to be made directly by the final "users" of the space in production. This points to the embedding of technical knowledge in interfaces so that the ends can be defined collectively in an informed way, breaking the false linearity between means and ends and questioning the common idea that ends can only be properly defined by those who are technically proficient with the related means. The analysis of several practical experiences of the use of parameterization shows that it transforms constraints into open variables, but in order to arrive at truly flexible solutions, a parametric space should not "crystallize" parameters explored during the conception phase of the design (as in parametricism), but must also contemplate at least two other levels of flexibility related to implementation and use. The incorporation of time and adaptability is pointed as key in this process and a possible path deals with the indirect production of space,structuring rules for urban interactions. The potential opening of the structure through parameterization techniques provides opportunities to rethink urban legislation in a moredemocratic way, since traditional rules tend to prescribe and direct urban development towards an idealized and preconceived scenario. Special attention is given to zoning laws, because they introduce the map as a fundamental element for differentiating rules applicable to different parts of the city. Its origins and international diffusion are revisited, as well some of the new models that seek to overcome limitations of the Euclidian approach but end up creating new problems. The thesis examines how these problems turn into obstacles for the autonomous production of urban space, grouping them into two general problems: the strengthening of centralization forces in urban planning, which ignores emerging forces that also plan and act in the production of space; and the mismatch between complexity of the structure (urban rules) and simplicity/prescription of the organization (outcomes). An analysis of cases that reject zoning shows that the mere elimination of this kind of law is not able to overcome some of the problems. The importance of reversing the logic of zoning in order to create a proper context for autonomy and variety-diversity is raised, speculating on of the use of the map in an inverted way in order to break with the centralization of planning and form alternative emergent decision-making structures, operating on smaller scales. In this scenario, interfaces could help expanding the imaginary and disclosing new possibilities. Two cases of parametric interfaces that help in the construction of alternative processes related to land use (VillageMaker and Play Oosterwold) are critically analyzed. The thesis is concluded with guidelines for future development of new interfaces that focus on metaplanning, in order to contribute to the experimentation of new ways of structuring collective decision processes related to land development and use.